Exploring the Physical, Chemical and Biological Components of Soil: Improving Soil Health for Better Productive Capacity - G. F. Sassenrath; K. Davis; A. Sassenrath-Cole; N. Riding (Kansas Agricultural Experiment Station Research Reports, 2018)
“Soil health” is a term that is used to describe soil quality. The U.S. Department of Agriculture’s Natural Resources Conservation Service has defined soil health as “The continued capacity of soil to function as a vital living ecosystem that sustains plants, animals and humans (NRCS 2018).” For a farmer, soil health is the productive capacity of the soil, or the capacity of the soil to produce a crop or pasture. Healthy soils produce more and with better quality. Soil health is critical for water and nutrient cycling. Soil captures rainwater and stores it for use by plants. Soil health is important to improve both the amount of water and nutrients that a soil can hold, and the availability of water and nutrients for plants. The storage of water and nutrients and subsequent transfer to plants are critical determinants of the productive capacity of the soil, and the soil health. Here, we explore the fundamental components of soil, and how each component contributes to soil health and soil productive capacity.
Keywords: Soil health; tillage; cover crops